2016
DOI: 10.7554/elife.12397
|View full text |Cite
|
Sign up to set email alerts
|

The Melanocortin Receptor Accessory Protein 2 promotes food intake through inhibition of the Prokineticin Receptor-1

Abstract: The Melanocortin Receptor Accessory Protein 2 (MRAP2) is an important regulator of energy homeostasis and its loss causes severe obesity in rodents. MRAP2 mediates its action in part through the potentiation of the MC4R, however, it is clear that MRAP2 is expressed in tissues that do not express MC4R, and that the deletion of MRAP2 does not recapitulate the phenotype of Mc4r KO mice. Consequently, we hypothesized that other GPCRs involved in the control of energy homeostasis are likely to be regulated by MRAP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 32 publications
5
82
1
Order By: Relevance
“…The actual role of MRAP in the modulation of MC3R-regulated food intake and body weight, however, is still up for debate. Recently, MRAP2 has also been demonstrated to play a role in the function of the prokineticin-1 and -2 receptors, suggesting this protein may be a modulator of multiple GPCRs (Chaly et al 2016), and exert effects on feeding and body weight through multifactorial effects.…”
Section: Pharmacological Complexities Of α-Msh Signalingmentioning
confidence: 99%
“…The actual role of MRAP in the modulation of MC3R-regulated food intake and body weight, however, is still up for debate. Recently, MRAP2 has also been demonstrated to play a role in the function of the prokineticin-1 and -2 receptors, suggesting this protein may be a modulator of multiple GPCRs (Chaly et al 2016), and exert effects on feeding and body weight through multifactorial effects.…”
Section: Pharmacological Complexities Of α-Msh Signalingmentioning
confidence: 99%
“…As with MRAP, MRAP2 also naturally exists as an antiparallel homodimer but with a distinct tissue expression pattern principally in many areas of the CNS (Chan et al 2009, Asai et al 2013, Chaly et al 2016. We demonstrated that MRAP2 interacted with all five of the melanocortin receptors in transfected cells (as does MRAP1) (Chan et al 2009).…”
Section: Mrap2mentioning
confidence: 80%
“…More recently, Chaly and coworkers (Chaly et al 2016) reported an interaction between the prokineticin 1 and 2 receptors (PKR1 and PKR2) and MRAP2, and an inhibitory effect of MRAP2 when expressed in vitro with these receptors (although a 10:1 ratio of MRAP2 to PKR1 or PKR2 expression vector was used). These findings are particularly interesting in the light of the Mrap2-knockout mouse studies.…”
Section: Are the Mraps Promiscuous?mentioning
confidence: 99%
“…Recently, PKR1 has been shown as the first non-melanocortin GPCR to be regulated by the melanocortin receptor accessory protein 2 (MRAP2). Indeed, MRAP2 significantly and specifically inhibits PKR1 signaling [16].…”
Section: Prokineticin-2 Is An Anorexigenic Peptidementioning
confidence: 99%